1986
DOI: 10.1111/j.1365-2605.1986.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in progressive motility and improved morphology of human spermatozoa following their migration through Percoll gradients

Abstract: Human spermatozoa were separated on the basis of their motility in a discontinuous Percoll-gradient made up in tissue culture medium containing 10% (v/v) human serum (TCMS). Portions of ejaculates were placed on top of the gradients. After 3 h at 37 degrees C the bottom 1.5 ml was collected and the sperm washed free of the Percoll solution by centrifugation at 240 X g after dilution in TCMS. In this way the spermatozoa were separated from seminal fluid by means of the swimming rate of the sperm. When semen sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…Although a proper consensus has not yet been established, it has become widely accepted that normal parameters, defined according to WHO criteria (1989) are associated with high percentages of fertilization and cleavage rates in IVF. Furthermore, many authors have concentrated their attention on the predictive value of morphology (Kruger et al, 1986;Pousette et al, 1986), and it is felt that normal morphology is indicative of normal function, while high levels of morphologically abnormal spermatozoa in the ejaculate are associated with a reduced fertilizing potential (Oehninger et al, 1988). When we compared the morphology and CMA 3 fluorescence in individual spermatozoa, we found a high frequency of CMA 3 positive nuclei among macrocephalic spermatozoa in both treatment groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although a proper consensus has not yet been established, it has become widely accepted that normal parameters, defined according to WHO criteria (1989) are associated with high percentages of fertilization and cleavage rates in IVF. Furthermore, many authors have concentrated their attention on the predictive value of morphology (Kruger et al, 1986;Pousette et al, 1986), and it is felt that normal morphology is indicative of normal function, while high levels of morphologically abnormal spermatozoa in the ejaculate are associated with a reduced fertilizing potential (Oehninger et al, 1988). When we compared the morphology and CMA 3 fluorescence in individual spermatozoa, we found a high frequency of CMA 3 positive nuclei among macrocephalic spermatozoa in both treatment groups.…”
Section: Discussionmentioning
confidence: 86%
“…In turn, it is generally accepted that an association exists between these semen parameters and fertilizing ability (Mahadevan and Trounson, 1984;Kiugeretal, 1986;Liu etal., 1988). Sperm morphology, in particular, seems to be the most significantly related parameter to fertilization rates (Pousette et al, 1986;Oehninger et al, 1988). With the advent of in-vitro fertilization (TVF) and related techniques such as subzonal insemination (SUZI) and intracytoplasmic sperm injection (ICSI), it has become increasingly apparent that the number, motility and morphology of spermatozoa are not always indicative of a male's fertility status.…”
Section: Introductionmentioning
confidence: 99%
“…The DGC method separates spermatozoa according to their density and favors the isolation of motile and morphologically normal spermatozoa [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, similar to the cervix and oviduct, Percoll may act as a challenging barrier for spermatozoa, operating as sperm selection technique for excluding sperm cells less capable in performing successful fertilization. There is good evidence that morphologically normal spermatozoa offer the best fertilizing potential (POUSETTE et al, 1986; VAN DER ZWALMEN et al, 1991;ARRUDA et al, 2011;OLIVEIRA et al, 2013). Van Der Zwalmen et al (1991) demonstrated that Percoll technique selects sperm samples with better morphological quality from normal as well as from poor semen samples.…”
Section: Resultsmentioning
confidence: 99%